PERUBAHAN PENDAPATAN MASYARAKAT DESA JIKO INDUK KECAMATAN MOTONGKAD, BOLAANG MONGONDOW TIMUR PADA MASA PANDEMI COVID 19 (Changes In Income of The Jiko Induk Village Communities Motongkad District, Bolaang Mongondow East during The Pandemic Covid 19) - Lucky Boy Jovfan Koroh; Theodora M. Katiandagho; Jelly R. D. Lumingkewas (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2022)
East Bolaang Mongondow is one of the areas that has begun to develop the tourism sector apart from agriculture, animal husbandry, services, mining and others. The tourism sector which was developed about three years ago before the outbreak of Covid 19, especially in Jiko Induk Village was the Abadi Beach, Tanjung Silar Beach and Cimoki Beach tourism. This has had the impact of decreasing tourist visits to Jiko Induk Village, which has resulted in decreased income for the people of Jiko Induk Village who work in the tourism sector. aims to describe changes in the condition of people's income in Jiko Induk Village both for people who work as farmers and fishermen as well as service sellers at tourist destinations Cimoki Beach, Abadi Beach and Tanjung Silar, namely by category before becoming a tourist destination, when it became a tourist destination and during the Covid 19 Pandemic. The research result showed that the category of changes in livelihood during the Covid 19 Pandemic illustrates that 13 respondents who have the profession of part-time workers, namely as fishermen and sellers of boat motorcycle taxi services, with a percentage of 43.33%, and people who have jobs as car driver renters, builders, yellow rice sellers and BRI Link Agents each had 1 respondent with a percentage of 3.33%. Thus the category of changes in the livelihoods of the Jiko Induk Village community experienced a significant change in livelihood when it became a tourist destination by opening new jobs for the Jiko Induk Village community.